EXPLORING PERINATAL DEATH CHARACTERISTICS AT DR. SOETOMO GENERAL HOSPITAL, SURABAYA FROM 2014 TO 2015 - JOEWONO, HERMANTO TRI; SULISTYONO, AGUS; WARDANI, RATIH; ADITIAWARMAN, (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: There are several risk factors for perinatal death. This study aimed to explore the characteristics of perinatal mortality at Dr. Soetomo General Hospital, Surabaya from 2014 to 2015.Methods: This was a descriptive study. Maternal and perinatal data were taken from the medical records. Results: The total perinatal death was 285 cases of all deliveries at Dr. Soetomo General Hospital, Surabaya in 2014-2015. Most women were in maternal age of 17-34 years. The maternal education was mostly high school, and most mothers were unemployed. More than a half of maternal parity was multigravida (63.5%), and the gestational age was preterm or under-month gestation at 81.4%. Most infants (73.3%) had low birth weight, and most cases were born vaginally. The majority of cases were non-booked case (NBC). Most of perinatal mortality was caused by prematurity followed by asphyxia, and the maternal factor was preeclampsia/eclampsia. Conclusion: Perinatal deaths mostly occurred in postnatal with the main causes of prematurity and asphyxia and the maternal factor was preeclampsia/eclampsia.